Hubungan Dukungan Teman Sebaya Dan Lingkungan Sekolah Dengan Upaya Pencegahan Anemia Pada Remaja Putri - Sajalia, Husniyati; R. Supini (ProHealth Journal, 2025)
Adolescent girls who experience anemia are at risk of becoming anemic women of childbearing age and continue to become mothers who experience chronic energy deficiencies during pregnancy. Chronic energy deficiency in pregnant women can increase the risk of stunted fetal growth, premature birth, and child growth and development disorders, including stunting. This study aimed to analyze the relationship between peer support and the school environment with efforts to prevent anemia in adolescent girls at MA Darussolihin NW Kalijaga. This study is an observational analytical study with a cross-sectional approach. A sample of 63 people was taken using a simple random sampling technique. The instruments used were questionnaires and data analysis using the Spearman rank test. The statistical test results showed a relationship between peer support (r=0.674, p-value=0.000) and the school environment (r=0.543, p-value=0.000) with efforts to prevent anemia in adolescent girls.